Międzynarodowa konferencja na temat oddziaływań troficznych w płytkich jeziorach słodko- i słonawowodnych- "Płytkie jeziora '98" (Blossin k. Berlina, 3-8 VIII 1998 r.) - Kufel, Lech (Oficyna Wydawnicza Instytut Ekologii PAN, 1999)
Strony 92-94 ; 24 cm
Keywords: hydrobiologia; konferencje

8. międzynarodowa konferencja na temat ochrony i zrównoważonego użytkowania jezior (Kopenhaga, 17-21 V 1999 r.) - Kufel, Lech (Oficyna Wydawnicza Instytut Ekologii PAN, 1999)
Strony 291-292, [1] karta kolorowych tablic ; 24 cm
Keywords: jeziora; ochrona; rekultywacja jezior; konferencje

Chlorophyll - nutrients - Secchi disc relationships in the Great Mazurian Lakes (North-Eastern Poland) - Kufel, Lech (Polish Academy of Sciences. Institute of Ecology. Publishing Office, 1998)
The relationships between SD, chlorophyll, total phosphorus and total nitrogen were analysed basing on data from 25 sites in 21 Great Mazurian Lakes collected during 12 years. Best fit for the data were reached when piecewise linear regression was used to approximate the relationship between chlorophyll and nutrient concentrations. The regression line divided the whole data set into two regions: lower, mesotrophic (chlorophyll < 20 mg m-3) where the response of chlorophyll to N and P was insignificant and higher, eutrophic (chlorophyll > 20 mg m-3) within which chlorophyll yield was proportional to nutrient increments. Except for trophic type, the relationship between chlorophyll and nutrients was affected by mixing type of lakes. No significant relationships between chlorophyll, nutrient concentrations and Secchi disc visibility were found in the shallow, polymictic lakes. Possible explanations for the observed effects including resuspension and grazing pressure on algae are proposed.
Strony 327-337 : ilustracje ; 27 cm
Bibliografia na stronach 335-337
Keywords: in - lake phosphorus; nitrogen; lake trophic type; mixing; chlorophyll : PP ratio; non-linear regression

Spotkanie naukowców z międzynarodowej sieci długoterminowych badań ekologicznych -LTER (Snowbird, USA, 1-5 VIII 2000 r.) - Kufel, Lech (Oficyna Wydawnicza Instytut Ekologii PAN, 2000)
Strony 321-323 ; 24 cm
Keywords: ekologia; długookresowe badania ekologiczne

Eutrofizacja jezior, czyli o niedostatkach pewnych modeli empirycznych i potrzebie spójnej koncepcji zjawiska - Kufel, Lech (Oficyna Wydawnicza Instytut Ekologii PAN, 2000)
This paper is aimed at focusing the Reader’s attention to some less considered or neglected aspects of lakę eutrophication. The weakness of the existing chlorophyll-nutrient models is demonstrated here by the apparent uncoupling of chlorophyll and nutrients in the Great Masurian Lakes and also in other lakes of the Polish lowland. The models seem to not recognise sonie specific properties of lakes, which vary along their trophic gradient. The first is a different type of nutrient cycling - dominated by vertical, cyclic and bimodal nutrient transport in eutrophic lakes versus morę conservative nutrient turnover restricted to the epilimnetic zonę and relying mostly on biotic recycling in oligo- and mesotrophic lakes. Secondly, the models do not consider the top-down effects of zooplankton, which in eutrophic lakes tend to reshape the algal structure towards the dominance of non-edible blue-green Cyanobacteria. This, in turn, would enhance accumulation of nutrients in epilimnia of eutrophic lakes and bimodal character of the nutrient turnover. Variable overlapping of abiotic and biotic factors in lakes along their trophic gradient make predictive power of the empirical models poor and calls for further insight and for a coherent theory of lakę eutrophication.
Strony 267-281 ; 24 cm
Bibliografia na stronach 278-280
Streszczenie w języku angielskim
Keywords: ekologia jezior; eutrofizacja jezior; fitoplankton; zooplankton; Wielkie Jeziora Mazurskie; biomasa glonów

Międzynarodowa konferencja na temat "Wykrywanie zmian środowiskowych. Nauka i społeczeństwo" (Londyn, 17-20 VII 2001 r.) - Kufel, Lech (Oficyna Wydawnicza Instytut Ekologii PAN, 2001)
Strony 312-314 ; 24 cm
Keywords: zmiany klimatyczne; konferencje

Seminarium na temat "Stacja regionalna kompleksowego monitoringu tła zanieczyszczenia środowiska lądowego wschodnioeuropejskiego podsystemu GEMS" (Żabinka, 11-13 IX 1985 r.) - Kufel, Lech (Państwowe Wydawnictwo Naukowe, 1986)
Strony 90-92 ; 24 cm
Keywords: Global Ecological Monitoring System; GEMS; konferencje

Watershed nutrient loading to lakes in Krutynia (Masurian Lakeland, Poland) system - Kufel, Lech (Polish Scientific Publishers, 1990)
Amounts of various forms of nitrogen and phosphorus as well as suspended solids and chlorides carried by waters of 17 streams were analysed. The seasonal dynamics of nutrient runoff from watershed was measured and the attempts undertaken to relate nutrient loading to the character of watershed drained by stream. In conclusion the effect of nutrient runoff on selected lakes was presented.
Strony 323-336 : ilustracje ; 24 cm
Bibliografia na stronach 335-336
Streszczenie w języku polskim
Keywords: nutrients; watershed; lake; runoff; agriculture; forest; wetlands

Spatial variability and long-term changes of the trophic parameters in the Great Masurian Lakes (Poland) - Kufel, Irena; Kufel, Lech (Polish Academy of Sciences. Institute of Ecology. Publishing Office, 1999)
Hydrologic division of the Great Masurian Lakes (North-eastern Poland) into the northern and southern drainage basin was found to be reflected in different trophic status of lakes. Chlorophyll (but not nutrient) concentrations in the northern part of the system were significantly lower than those in lakes of the southern part. It has been shown that tunnel-valley lakes (numerous in the southern watershed) appear to be more eutrophied in terms of chlorophyll abundance than morainic stratified lakes. Hypolimnetic enrichment and internal loading were probably responsible for the lack of in-lake phosphorus and chlorophyll decline in spite of the evident decrease of the external nutrient loading which had taken place between 1985 and 1996. Such a positive response was observed, however,in the case of nitrogen. Only in a hypertrophic Lake Niegocin some symptoms of recovery were noted after reduction of external point source pollution.
Strony 323-333 : ilustracje ; 27 cm
Bibliografia na stronach 332-333
Keywords: chlorophyll; nutrients; internal loading; lake response

Does biotic patchiness in a lake conform to chemical heterogeneity? - Kufel, Irena; Kufel, Lech (Polish Academy of Sciences. Institute of Ecology. Publishing Office, 2001)
Analyses of lake water taken in discrete sites along a c. 2 km transect from a 1 m depth in a eutrophic Lake Mikołajskie revealed a uniform horizontal distribution of temperature and oxygen concentrations. Conductivity, soluble reactive phosphorus and particularly chlorophyll concentrations showed, however, a marked variability along the transect. Significant correlation between pH and conductivity suggests that a local photosynthetically induced calcite precipitation may be responsible for the observed horizontal variability of these parameters. Biotic response (inferred from chlorophyll concentrations) was not coupled with chemical differences. Different temporal scales of chemical processes and phytoplankton growth are assumed to explain this discrepancy.
Strony 427-430 : ilustracje ; 27 cm
Bibliografia na stronie 430
Keywords: nutrients; chlorophyll; spatial and temporal variability

In situ decomposition of Phragmites australis Trin. ex Steudel and Typha angustifolia L. - Kufel, Irena; Kufel, Lech (Polish Scientific Publishers, 1988)
Decomposition of reed and cattail was measured in situ by standard net bag method. The rate of decomposition and release of nutrients, macroelements and heavy metals was analysed. The influence of nitrogen content and the N: P ratio on the process is suggested. The differences in decomposition rates and release of elements between plants or plant parts are presented and possible mechanisms of release are discussed in relation to particular element analysed.
Strony 459-470 : ilustracje ; 24 cm
Bibliografia na stronie 470
Streszczenie w języku polskim
Keywords: reed; cattail; decomposition; release; nutrients; heavy metals

Structure of submerged littoral vegetation in relation to pelagic trophic state indices - Kufel, Lech; Królikowska, Joanna; Kufel, Irena (Oficyna Wydawnicza Instytutu Ekologii PAN, 1996)
An attempt was undertaken to compare pelagic indices commonly used to describe trophic status of lakes (SD, chlorophyll, total phosphorus and total nitrogen) with parameters characterising submerged littoral zone of lakes (maximum depth of plant occurrence, number of species, mean plant biomass and percentage biomass of the dominating species). The data were collected from 20 lakes of various morphometry and trophic state selected from the Great Masurian Lakes system (north-eastern Poland) from 1985 till 1995. The greatest impact on submerged littoral structure (species abundance and diversity) was exerted by water transparency, nutrient concentrations had negligible effect on littoral parameters. From among four littoral characteristics, submerged plant biomass seems to be of the poorest indicative value since its correlation with pelagic indices was usually weakest and statistically insignificant.
Strony 299-310 : ilustracje ; 24 cm
Bibliografia na stronach 309-310
Streszczenie w języku polskim
Keywords: lake littoral; submerged macrophytes; species composition; nutrients; chlorophyll; water transparency